2021
DOI: 10.1002/ptr.7340
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of black myrobalan on cognitive, positive, and negative symptoms in patients with chronic schizophrenia: A randomized, double‐blind, placebo‐controlled trial

Abstract: Schizophrenia, as a chronic and disabling mental disorder, causes a wide range of symptoms, including cognitive impairments, positive, negative, and mood symptoms. There are no effective treatments for cognitive symptoms. Black myrobalan (Terminalia chebula Retz.), a medicinal plant of the Combretaceae family, exerts antioxidant, antiacetylcholinesterase, and anti‐inflammatory effects. These effects can lessen the symptoms of schizophrenia. So, this study was conducted to evaluate black myrobalan's impact on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Regarding posttest and the follow up test, the same figure indicates that, the percentage of subjects who have low social functioning is decreased to (2% and 0% respectively), while the percentage of subjects who have high social functioning is increased to (44%). Tables (2) shows highly statistically significant differences between pre, post, and follow up with P-value (0.0001*) regarding the total social functioning score, which was increased to (153.7±24.8) at the post-test. While, at the follow up, it was (151.1±19.8).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Regarding posttest and the follow up test, the same figure indicates that, the percentage of subjects who have low social functioning is decreased to (2% and 0% respectively), while the percentage of subjects who have high social functioning is increased to (44%). Tables (2) shows highly statistically significant differences between pre, post, and follow up with P-value (0.0001*) regarding the total social functioning score, which was increased to (153.7±24.8) at the post-test. While, at the follow up, it was (151.1±19.8).…”
Section: Resultsmentioning
confidence: 91%
“…The fifth edition of the Diagnostic and Statistical Manual of Mental Disorders recognized that schizophrenia is characterized by five-dimensional psychotic symptoms. These symptoms are organized by category as positive symptoms, negative symptoms, cognitive deficits, mood issues, and signs of disorganization [2] . In addition, impaired social functioning is one of the detrimental symptoms and a key component of schizophrenia [3] .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that Terminalia chebula in black salt could be a valuable ingredient in improving joint health and well-being. Besides, a study found that Terminalia chebula had significant cognitive benefits for patients with chronic schizophrenia [38]. This research suggests that the antioxidant, anti-acetylcholinesterase, and antiinflammatory properties of Terminalia chebula may offer potential natural treatment options for cognitive and behavioral symptoms related to psychiatric conditions like schizophrenia.…”
Section: Health Benefits Of Harad (Terminalia Chebula) In Black Saltmentioning
confidence: 82%
“…However, it is not more prevalent in SLE in comparison with the rest of autoimmune conditions [35]. Studies have also detected a positive linkage between SLE and the danger of being affected by schizophrenia [36,37].…”
Section: Psychosismentioning
confidence: 99%